Traditional Chinese Medicine Extract from Huaier Increases the Expression of Duffy Antigen Receptor for Chemokines and Reduces the Expression of Its Ligands - Ying Chen; Qianjun Chen; Fengfeng Xie; Hui Peng; Yanlan Wu; Shaowen Zhong; Zhiyu Wang; Wenxia Li; Wanjun Xie (Analytical Cellular Pathology)
Aims. The aim of the present study is to investigate whether the aqueous extract from Huaier, a traditional Chinese medicine (TCM), can affect the expression of Duffy antigen receptor for chemokines (DARC) and its ligands. Moreover, we compare the status of DARC in primary and metastatic breast cancer tissues from the same patient. Methods. Immunohistochemistry was used to detect the expression of DARC in primary and metastatic focuses in 30 patients with breast cancer. The effect of Huaier aqueous extract on the expression of DARC and its ligands was investigated by quantitative real-time polymerase chain reaction, Western blotting, and enzyme-linked immunosorbent assay. Results. The expression score of DARC in primary focuses was significantly higher than that in metastatic focuses, while changes of ER, PR, and HER2 receptors were not significantly different between primary and metastatic focuses. Huaier aqueous extract promoted the expression of DARC and reduced the secretion of CC chemokine ligand 2 (CCL-2), CXC chemokine ligand 8 (CXCL-8, IL-8), matrix metalloproteinase 2 (MMP-2), and CXC chemokine ligand 1 (CXCL-1). Conclusion. The present study demonstrates that difference in expression level of DARC between primary and metastatic focuses of breast cancer was significant, while differences in expression of ER, PR, and HER2 between primary and metastatic focuses were not significant. DARC may play a negative role in the metastasis of breast cancer. Traditional Chinese medicine extract from Huaier can increase DARC expression and reduce the expression of its ligands such as CCL-2, IL-8, MMP-2, and CXCL-1.